Is He Playing Solo or within an Ensemble? How the Context, Visual Information, and Expertise May Impact upon the Perception of Musical Expressivity. (August 2014) - Glowinski, Donald; Riolfo, Arianna; Shirole, Kanika; Torres-Eliard, Kim; Chiorri, Carlo; Grandjean, Didier
Visual information is imperative when developing a concrete and context-sensitive understanding of how music performance is perceived. Recent studies highlight natural, automatic, and nonconscious dependence on visual cues that ultimately refer to body expressions observed in the musician. The current study investigated how the social context of a performing musician (eg playing alone or within an ensemble) and the musical expertise of the perceivers influence the strategies used to understand and decode the visual features of music performance. Results revealed that both perceiver groups, nonmusicians and musicians, have a higher sensitivity towards gaze information; therefore, an impoverished stimulus such as a point-light display is insufficient to understand the social context in which the musician is performing. Implications for these findings are discussed.